Silicona poliláctica - Ortiz, C.; Rubio, L.; Padrón, O.; Díaz, J. (Ingenia Materiales, 2019)
Silicone is a polymer whose structure is the unión of long strings of silicone and oxygen. The aim of our project will be the modification of this polymer fas a base material) to which it will be added different additives to improve its properties compared to those of the primitive material. With this we want to obtain a new material that must be easy to use and that contributes better results than the "puré" silicone, that is, without having incorporated any additive. Focused especially for everyday and domestic use